Inhibitors of acid secretion can benefit gastric wound repair independent of luminal pH effects on the site of damage. Issue 6 (13th October 2011) - Demitrack, Elise S; Aihara, Eitaro; Kenny, Susan; Varro, Andrea; Montrose, Marshall H
Abstract : Background and aims: The authors' goal was to measure pH at the gastric surface (pHo ) to understand how acid secretion affects the repair of microscopic injury to the gastric epithelium. Methods: Microscopic gastric damage was induced by laser light, during confocal/two-photon imaging of pH-sensitive dyes (Cl-NERF, BCECF) that were superfused over the mucosal surface of the exposed gastric corpus of anaesthetised mice. The progression of repair was measured in parallel with pHo . Experimental conditions included varying pH of luminal superfusates, and using omeprazole (60 mg/kg ip) or famotidine (30 mg/kg ip) to inhibit acid secretion. Results: Similar rates of epithelial repair and resting pHo values (∼pH 4) were reported in the presence of luminal pH 3 or pH 5. Epithelial repair was unreliable at luminal pH 2 and pHo was lower (2.5±0.2, P <0.05 vs pH 3). Epithelial repair was slower at luminal pH 7 and pHo was higher (6.4±0.1, P <0.001). In all conditions, pHo increased adjacent to damage. At luminal pH 3 or pH 7, omeprazole reduced maximal damage size and accelerated epithelial repair, although only at pH 3 did omeprazole further increase surface pH above the level caused by imposed damage. At luminal pH 7, famotidine also reduced maximal damage size and accelerated epithelial repair. Neither famotidine nor omeprazole raised plasma gastrin levels during the time course of the experiments. Conclusions: Epithelial repair in vivo is affected by luminal pH variation, but the beneficial effects of acutely blocking acid secretion extend beyond simply raising luminal and/or surface pH.